Pengaruh Penerapan Media Pembelajaran Etnomatematika Berbasis Mobile terhadap Hasil Belajar Matematika Siswa SMP pada Materi Bangun Datar - Sri Purwandaningsih Waluya; Evi P. Hulukati; Auli Irfah (Lembaga Pengembangan Kinerja Dosen, 2026)
Mathematics is frequently regarded as a demanding discipline due to its abstract concepts, which are hard for students to grasp visually. Therefore, the implementation of proper learning media is necessary to help students build a deeper understanding of abstract mathematical concepts, particularly in quadrilaterals, enabling these concepts to be comprehended more concretely. The present study seeks to examine the effect of mobile-based ethnomathematics learning media on students' mathematics achievement in the topic of plane figures at SMP Negeri 1 Botupingge. A quasi-experimental approach using a Pre-test–Post-test Control Group Design was applied, with 38 students as the research sample, consisting of class VII C assigned the experimental group and class VII A allocated to the control group, identified through a cluster random sampling approach. The experimental group utilized mobile-based ethnomathematics media combined with the Problem Based Learning (PBL) model, whereas the control group used PowerPoint media with the same PBL model. Data was carried out by administering pre-tests and post-tests in essay form to assess students' mathematics achievement on quadrilaterals. The findings reveal that mobile-based ethnomathematics learning media significantly improves students' mathematics achievement, making learning more relevant to students' local life and culture.